Manajemen Integrasi Kurikulum Ketakhassusan dan Kurikulum Merdeka dalam Meningktkan Mutu Lulusan - Hidayat, Muhamad Yusuf; Santosa, Sedya; Aulia, Nur Annisa (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This study aims to examine how the management of the unique curriculum and the Merdeka curriculum can improve the quality of school graduates, thereby increasing the quality of school education. Using a qualitative approach, this study collected and analyzed data from interviews, observations, and documentation on matters related to the integrated management of the unique curriculum and the Merdeka curriculum. This research process used source triangulation techniques, namely collecting data sources from several informants and then validating the data. In this model, it is explained that: First, planning is carried out using a pattern combining administrative, arena, and inverted models. Second, implementation is carried out by developing two models: a fragmented model in scientific disciplines and learning subunits and a shared model between scientific disciplines and learning. Third, the evaluation is developed using the Stufflebeam's evaluation model, without including curriculum context assessment. Thus, the results of the overall assessment serve as the basis for continuous reformulation of curriculum integration management. In addition, several aspects of learning outcomes are evaluated in terms of psychomotor and student effectiveness. From these two assessments, an integrated assessment system is developed.